Konsep Hukum Hooke melalui Strategi Index Card Match Berbasis Kooperatif Guna Peningkatan Keahlian Berpikir Analitis Siswa Kelas XI IPA3 SMAN 2 Lhokseumawe - Evidianti (Yayasan Kawanad, 2023)
The implementation of the Hooke's Law concept through the Cooperative-based Index Card Match Strategy proves to be an effective learning approach in enhancing students' understanding. This research contributes to the development of innovative teaching methods that can be utilized to strengthen students' critical thinking skills at the high school level. The study involved 30 students from the eleventh-grade science class, with each undergoing 2 cycles or 3 meetings. The Hooke's Law concept serves as the primary foundation for instruction, where students engage in learning activities involving index cards to gain a profound understanding of material elasticity. The Index Card Match Strategy is employed to stimulate collaboration and interaction among students in comprehending the concept. This research adopts a qualitative approach, implementing the classroom action research method. The results indicate a significant improvement in students' critical thinking skills after the application of the Index Card Match Strategy. Students not only can identify and comprehend the principles of Hooke's Law but also can relate this concept to real-life applications.